Concomitant B Hairy Cell Leukemia and Mycosis Fungoides in an Elderly Man - Eric Wong; Muhammad N. Mahmood; Thomas G. Salopek (Karger Publishers, 2017)
The development of both a T- and B-cell lymphoproliferative disorder in one patient is an unlikely coincidence due to the low prevalence of each malignancy. We report a 65-year-old man with a previously documented history of B hairy cell leukemia, who presented with a new-onset acneiform eruption of his scalp, face, trunk, back, and extremities. Routine pathology of the skin lesions with immunohistochemical stains and molecular studies were consistent with a folliculotropic mycosis fungoides. B hairy cell leukemia and mycosis fungoides occurring in the same patient seems to be a rare phenomenon with only 5 cases reported in the literature.